INVESTIGATION OF PECULIAR FEATURES PERTAINING TO FORMATION OF BORIDE COATINGS ON CARBONITRATED LOW-CARBON STEEL - V. F. Protasevich; G. V. Stasevich (Наука и техника)
The paper contains description about obtaining two-phase boride coatings on preliminary carbonitrated steel 20. The influence of a preliminary carbonitration on phase – and structure formation and properties of the boride coatings has been investigated in the paper.